Effect of Sitting Position on Equal-dose Spinal Anesthetic for Cesarean Section and Postpartum Tubal Ligation. Issue 2 (June 2015) - Kwok, S.C.; Teoh, W.H.; Ithnin, F.
<x xml:space="preserve">Abstract</x> (Acta Anaesthesiol Scand. 2014;58(6):743–750)